eCM 2014
DOI: 10.22203/ecm.v027a02
|View full text |Cite
|
Sign up to set email alerts
|

Repair of critical-sized bone defects with anti-miR-31-expressing bone marrow stromal stem cells and poly(glycerol sebacate) scaffolds

Abstract: The repair of critical-sized defects (CSDs) is a significant challenge in bone tissue engineering. Combining the use of progenitor cells with gene therapy represents a promising approach for bone regeneration. MicroRNAs play important roles in most gene regulatory networks, regulate the endogenous expression of multiple growth factors and simultaneously modulate stem cell differentiation. Our previous study showed that knocking down miR-31 promotes the osteogenesis of bone marrow stromal stem cells (BMSCs). To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 57 publications
0
57
0
2
Order By: Relevance
“…in the expression of osteogenic lineage genes in in vitro studies, and bone formation was detected in vivo [143].…”
Section: Bone Formation Attempts Using Mscsmentioning
confidence: 99%
“…in the expression of osteogenic lineage genes in in vitro studies, and bone formation was detected in vivo [143].…”
Section: Bone Formation Attempts Using Mscsmentioning
confidence: 99%
“…For example, inhibiting endogenous miR-31 significantly increases the osteogenic potential of bone mesenchymal stem cells (BMSCs) [136]. In one demonstration, Deng et al lentivirally-transfected BMSCs to express anti-miR-31 and observed a 2.5-fold increase in expression of special AT-rich sequence-binding protein 2, a protein involved in osteoblastic differentiation and bone development [137]. This increased expression was maintained in vitro at a relatively constant level between 4 and 21 days after treatment [137].…”
Section: Regenerative Medicine Targetsmentioning
confidence: 99%
“…In one demonstration, Deng et al lentivirally-transfected BMSCs to express anti-miR-31 and observed a 2.5-fold increase in expression of special AT-rich sequence-binding protein 2, a protein involved in osteoblastic differentiation and bone development [137]. This increased expression was maintained in vitro at a relatively constant level between 4 and 21 days after treatment [137]. To determine whether modulation of miR-31 activity in BMSCs affected CSD repair in vivo , BMSCs were transfected in vitro with anti-miR-31 containing vectors, seeded 24 hours later onto poly(glycerol sebacate) (PGS) scaffolds, and then implanted into 8 mm rat calvarial CSDs.…”
Section: Regenerative Medicine Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…O miR-146a e o -146b também são relevantes, uma vez que regulam negativamente a SMAD7 (banco de dados GeneCards e TargetScanhttp://www.genecards.org / http://www.targetscan.org). Quanto aos miRs regulados negativamente pela membrana de P(VDF-TrFE)/BT, o miR-31 é considerado um inibidor da osteogênese (Deng et al, 2014) e possui um papel importante na osteoclastogênese e no controle da reabsorção óssea (Baglio et al, 2013). Os resultados iniciais são promissores e novos experimentos são necessários para a avaliação funcional de miRs que possam estar envolvidos com o potencial osteogênico da membrana de P(VDF-TrFE)/BT.…”
Section: Discussionunclassified